Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) terhadap Peningkatan Hasil belajar Mekanika Teknik Siswa di SMK Negeri 2 Bojonegoro - Mustikasari, Septiana; Supardji, Supardji (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyse the influence of the Contextual Teaching and Learning (CTL) learning model on improving student learning outcomes in Engineering Mechanics subjects. CTL is a learning approach that relates academic material to real-world situations, so that students can more easily understand concepts and apply them in everyday life. The research population is class X students of the building engineering expertise program at SMK Negeri 2 Bojonegoro, which includes an understanding of the concept of Engineering Mechanics, as well as observation sheets of student learning activities. The results show that the application of the CTL model significantly improves student learning outcomes. Students who learn with the CTL model also show higher active engagement during the learning process. Based on these findings, the CTL model is recommended to be applied in the learning of Engineering Mechanics, as it can help students understand the concepts in depth and relevant to practical applications in the construction world.